DOES MENTAL WORKLOAD AFFECT MISSED NURSING CARE IN NURSES? A CROSS-SECTIONAL AND CORRELATIONAL STUDY - Hande Demirtaş; Serap Altuntaş; Nazlıhan Efe Sayan (International Journal of Health Services Research and Policy, 2025)
This cross-sectional and correlational study was conducted to determine the effect of mental workload of nurses on missed nursing care. The study was conducted with 93 volunteer nurses working in a training and research hospital. Descriptive information form, mental workload scale, missed nursing care needs scale were used for data collection.In this study, it was found that the mean mental workload scores of nurses were high and the mean missed nursing care scores were low. It was determined that there was no significant relationship between temporary workload, emotional workload, performance-related workload and total mental workload of nurses and the amount and causes of missed nursing care needs (p>0.05), and there was no significant relationship between cognitive workload and the causes of missed nursing care needs (r= -.105, p= .318), but there was a negative, significant and very weak relationship with the amount of missed nursing care needs (r=-.226, p= .029). It was also found that cognitive workload explained 5.1% of the amount of missed nursing care needs in nurses. As a result of this study, it was revealed that temporary, emotional, performance-related and total mental workload did not affect the amount and causes of missed nursing care needs in nurses, while cognitive workload only reduced the amount of missed nursing care needs. According to these results, in order to reduce the mental workload of nurses, more nurses should be employed in health institutions and other undesirable organizational outcomes such as possible exhaustion, job dissatisfaction, fatigue, etc. should be prevented.